Signifikansi Penerapan Metode Pembelajaran Project-based Learning dan Roleplay Negosiasi Arsitek-Klien dalam Pembelajaran Mahasiswa Arsitektur - Yuli, Nensi Golda (Universitas Islam Indonesia, 2024)
The experience of designing is often hindered by a lack of in-depth knowledge of construction approaches and negotiation skills with clients. This study tested client negotiation skills and understanding of three construction approaches—traditional, commercial, and behavioral—among Architecture students in the Building Culture course. This course has significant potential to be developed using innovative methods and learning content that closely align with the practice of architecture itself. The aim is to provide students with a deeper understanding based on real-world projects and negotiation skills through collaborative learning with lecturers on campus and practitioners. The method employed was project-based learning combined with role-playing, involving professional architects in 6 out of 14 course sessions. The research observation method included direct observation of student and practitioner activities during 14 classroom sessions and analysis of student reflection documents. The findings indicate that the two methods used in the learning process enhanced student engagement in class, satisfaction with the material studied, and direct learning experiences with practitioners. However, the study faced limitations in consistently bringing practitioners into the classroom. As a recommendation for future development, it is suggested to include more sessions focused on soft skills to better prepare students for the professional world.